2022
DOI: 10.5588/ijtld.21.0412
|View full text |Cite
|
Sign up to set email alerts
|

TB prevalence among patients with diabetes in Bangladesh

Abstract: OBJECTIVE: 1) To assess the prevalence of TB among patients with diabetes mellitus (DM) attending diabetic care centres in Bangladesh, and 2) to compare TB- and DM-related sociodemographic and other factors in diabetic patients who had TB and those who did not.METHODS: This cross-sectional study was conducted from 1 June 2019 to 31 March 2020 in 108 centres of the Diabetic Association of Bangladesh (BADAS), with a sample size of 3,649 patients with DM. Data were collected by face-to-face interview using semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Several studies conducted in India demonstrated that screening for TB among DM patients was feasible in India, where the DM epidemic continues to rise [ 46 , 58 ]. Similarly, a study conducted in Bangladesh indicated that TB screening among DM patients was also feasible [ 59 ]. It aligns with a pilot project study of TB-DM screening among patients visiting clinics in China, showing it was also feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted in India demonstrated that screening for TB among DM patients was feasible in India, where the DM epidemic continues to rise [ 46 , 58 ]. Similarly, a study conducted in Bangladesh indicated that TB screening among DM patients was also feasible [ 59 ]. It aligns with a pilot project study of TB-DM screening among patients visiting clinics in China, showing it was also feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of additional risk factors should be considered in prioritizing patients for routine chest X-ray screening. In Bangladesh, for example, female patients and those with undernutrition were found to be at higher risk of developing TB [30] . The higher TB rate in our study is in line with the general global trend that TB burden is higher among males [31] , but the Bangladesh finding of a higher TB rate among female patients with diabetes is in sharp contrast to ours.…”
Section: Discussionmentioning
confidence: 99%